2006
DOI: 10.1152/ajprenal.00261.2005
|View full text |Cite
|
Sign up to set email alerts
|

l-NAME, a nitric oxide synthase inhibitor, diminishes oxidative damage in urinary bladder partial outlet obstruction

Abstract: Partial bladder outlet obstruction (PBOO) results in cellular damage due to ischemia and reperfusion injury. Our study seeks to establish how early this damage can occur and the role that nitric oxide may play in its pathophysiology. Surgical PBOO (1, 3, and 7 days) were performed on male New Zealand White rabbits. Half of the animals were premedicated for 3 days with N(G)-nitro-l-arginine methyl ester(l-NAME), an inhibitor of nitric oxide synthase before obstruction. Bladder weight increased with duration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 22 publications
2
45
2
Order By: Relevance
“…L-NAME has been shown in other studies of bladder function to enhance ischemia damage at 1 day after PBOO but protected the bladder from nitric oxide-generated free radical damage at the later time periods [12]. This is different to what we found in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…L-NAME has been shown in other studies of bladder function to enhance ischemia damage at 1 day after PBOO but protected the bladder from nitric oxide-generated free radical damage at the later time periods [12]. This is different to what we found in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been demonstrated that NO-related damage due to nitrotyrosine was elevated with PBOO (23). Pretreatment with N G -nitro-L-arginine methyl ester (L-NAME), which acts as a competitive inhibitor of NOS, significantly inhibited the generation of nitrotyrosine (8). Also, reports by Saito et al (30 -32) showed that treatment with L-NAME can reduce apoptosis induced by I/R in the bladder and significantly increase the contractile responses compared with the I/R group without L-NAME.…”
mentioning
confidence: 99%
“…This observation confirms previous findings that in animal models and in patients suffering from bladder outflow obstruction, there is damage to the autonomic innervation (Sibley, 1987;Williams et al, 1993;Brading, 1997;Levin et al, 2000;de Jongh et al, 2009). Oxidative stress due to ischemia followed by reperfusion, has been demonstrated in obstructed bladders and may underlie the changes in muscle function and patchy denervation of the detrusor (Conners et al, 2006;de Jongh et al, 2009;Scheepe et al, 2011). There was no inhibition of bethanechol-induced responses (up to 10 -5 -M) in obstructed guinea pig bladders compared to shams or controls.…”
Section: Efs and Effect Of Cholinergic Agonists In Obstructionmentioning
confidence: 86%
“…The mechanism responsible for increased residual volume and bladder capacity in obstruction is still unclear. Oxidative damage to the autonomic innervation and to the detrusor muscle, demonstrated in animal models of bladder obstruction (Conners et al, 2006;de Jongh et al, 2009;Scheepe et al, 2011) could be involved. It has been recently shown that distension-sensitive bladder afferents had higher threshold volumes and lower tension sensitivity in obstructed rats (Zeng et al, 2012).…”
Section: Other Factors Influenced Obstruction-induced Bladder Overactmentioning
confidence: 99%